Implementation of the Subsidized Fertilizer Distribution Program through Farmer Cards in Galung Village, Barru District, Barru Regency - Zulhayyir, Zulhayyir; Nurlia, Nurlia (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the implementation of the subsidized fertilizer distribution program through Farmer Cards in Galung Village, Barru District, Barru Regency. This program is one of the government's efforts to digitize fertilizer subsidy distribution to make it more targeted, transparent, and efficient. The research method used was a qualitative approach, with data collection techniques through in-depth interviews, field observations, and documentation. The results indicate that the implementation of the Farmer Card program in Galung Village still faces various obstacles, including farmers' limited understanding of card use, uneven card distribution, and technical issues with the electronic system used. Nevertheless, this program is considered capable of providing a new direction for more controlled and data-driven fertilizer subsidy distribution. This study recommends the need for more extensive outreach, increased farmer capacity in using Farmer Cards, and improvements to the support system to achieve equitable and sustainable subsidized fertilizer distribution.